EVALUATION OF THE RATIONALITY OF CLAIMS MADE IN DRUG PROMOTIONAL LITERATURE IN WEST CHENNAI - Sekar, Pavithira; Sekar, Pavithira; Punnagai, K. (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The study was aimed to evaluate the adequacy of information provided by drug promotional literature using WHO criteria. They were also evaluated for the quality, types of claims and the genuineness of these claims in this literature. Methods: 412 drug promotional literature were collected from 20 busy physicians in the western part of Chennai from their private clinics. In addition to carrying out of WHO criteria, 1988,â€ the brochures were examined for the quality of coverage using a pre-tested and pre-validated checklist and types of claims and the genuineness of these claims were evaluated for their recoverability and accuracy. Results: It was found that all the WHO criteria were not fulfilled by any of the promotional literature. 91.2% of leaflets satisfied the 4 WHO criteria namely, the brand name, generic name, approved therapeutic uses, name and address of the manufacturer. A most neglected aspect of drug promotion was information regarding drug interactions, precautions, Adverse drug reactions and overdosage (<10%). Of 412 leaflets collected, the quantitative research methods were mentioned in 67 (16.2%). Cardiovascular drugs and nutritional supplements were the most promoted drug groups (23% and 17%, respectively). 412 drugs promotional literature made a total of 954 claims. References were cited in 47% of the literature of which 96% were from the indexed journal and were retrievable. Conclusion: Drug promotional literature analyzed by this study was inadequate in terms of their adequacy, quality and genuineness of coverage. Thus, the pharmaceutical companies did not follow the WHO guidelines while promoting their products, thus aiming to satisfy their commercial motive rather than fulfilling the educational aspect of promotion. Keywords: Promotional literature, Ethical criteria for drug promotion, Pharmacy practice, marketing practice.